Organization and Evolution of Drosophila Terminin: Similarities and Differences between Drosophila and Human Telomeres - Raffa, Grazia D.; Cenci, Giovanni; Ciapponi, Laura; Gatti, Maurizio (Frontiers in Oncology, 2013)
Drosophila lacks telomerase and fly telomeres are elongated by occasional transposition of three specialized retroelements. Drosophila telomeres do not terminate with GC-rich repeats and are assembled independently of the sequence of chromosome ends. Recent work has shown that Drosophila telomeres are capped by the terminin complex, which includes the fast-evolving proteins HOAP, HipHop, Moi and Ver. These proteins are not conserves outside Drosophilidae and localize and function exclusively at telomeres, protecting them from fusion events. Other proteins required to prevent end-to-end fusion in flies include HP1, Eff/UbcD1, ATM, the components of the Mre11-Rad50-Nbs (MRN) complex, and the Woc transcription factor. These proteins do not share the terminin properties; they are evolutionarily conserved non-fast-evolving proteins that do not accumulate only telomeres and do not serve telomere-specific functions. We propose that following telomerase loss, Drosophila rapidly evolved terminin to bind chromosome ends in a sequence-independent manner. This hypothesis suggests that terminin is the functional analog of the shelterin complex that protects human telomeres. The non-terminin proteins are instead likely to correspond to ancestral telomere-associated proteins that did not evolve as rapidly as terminin because of the functional constraints imposed by their involvement in diverse cellular processes. Thus, it appears that the main difference between Drosophila and human telomeres is in the protective complexes that specifically associate with the DNA termini. We believe that Drosophila telomeres offer excellent opportunities for investigations on human telomere biology. The identification of additional Drosophila genes encoding non-terminin proteins involved in telomere protection might lead to the discovery of novel components of human telomeres.